REDESAIN SUMBER BELAJAR PENDIDIKAN AGAMA ISLAM: BERWAWASAN MODERASI BERAGAMA DI ERA DISRUPSI INFORMASI - Dilla Muckti Jihansyah; Dinifath Fitriani; Muhammad Zaini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of digital technology has changed the way students obtain and understand religious information. The dominance of social media algorithms through the phenomenon of filter bubbles and echo chambers has the potential to limit exposure to the diversity of religious perspectives. On the other hand, the study of religious moderation in Islamic Religious Education (PAI) is still dominated by curriculum analysis and textbooks so that it has not accommodated much of the digital experience of students. This research aims to develop a framework for redesigning PAI learning resources with a religious moderation perspective that is responsive to the era of information disruption. The research uses a conceptual literature review approach with data sources in the form of academic literature obtained from Google Scholar, Scopus, Dimensions, and Garuda. Data were analyzed using content analysis and conceptual synthesis to identify themes, patterns, and relationships between concepts relevant to religious moderation, digital algorithms, learners' learning experiences, and learning resource development. The results of the study show three main findings, namely: (1) the study of religious moderation in PAI is still oriented to the textual dimension; (2) digital algorithms influence the formation of religious understanding through the personalization of information that has the potential to narrow the diversity of perspectives; and (3) there is a phenomenon of curriculum decoupling that shows the gap between the value of moderation in the curriculum and the digital reality of students. Based on these findings, this study offers a framework for redesigning PAI learning resources consisting of Cyber-trigger, Scaffolded Ikhtilaf, Reflective-Dialogic Inquiry, and Authentic Moderation Assessment. This framework contributes to strengthening the relevance of contextual, reflective, dialogical, and adaptive religious moderation learning to the challenges of the digital era. Keywords: Islamic Religious Education, religious moderation, learning resources, digital algorithms, information disruption.